Letenje demona u slovenskom folkloru i književnostima 19. veka Das Fliegen von Demonen in der slawischen Volksüberlieferung und Literatur des 19. Jahrhunderts - Ajdačić, Dejan (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author analyses the characteristics of the flight of demons in the folklore and 19th century literature of the Eastern and Southern Slavs.